RECONSTRUCTION OF THE NATIONAL FINANCIAL AUDIT INSTITUTIONAL SYSTEM FOR OPTIMIZING STATE LOSS MITIGATION - Muhammad Padol; Radian Salman (Jurnal Hukum Samudra Keadilan, 2024)
This article aims to establish a better institutional system for the national financial audit as part of the government's efforts to create a clean state free from financial abuse and corruption. Normatively, the Supreme Audit Agency (BPK) plays a crucial role based on Article 23 paragraph (5) of the 1945 Constitution. However, its singular existence changed after the formation of the Audit Board of the Republic of Indonesia (BPKP) through Presidential Regulation Number 192 of 2014, which became part of the Government Internal Supervisory Apparatus. From these normative issues arose a controversial case involving land procurement for a Palm Oil Plantation in Southwest Aceh, resulting in a dualistic determination of state losses between BPK and BPKP. The novelty of this article, compared to existing ones, lies in its reinforced analysis through comparisons with financial supervisory institutions in Japan (Board of Audit), the United States (GAO), and Australia (ANAO). The research employs a normative legal research method to examine principles and norms in positive law. It utilizes statutory, conceptual, and comparative approaches. In the context of financial oversight in Indonesia, both external and internal supervisory institutions, such as BPK and BPKP, play a vital role in ensuring efficiency, transparency, and accountability in financial management. Despite differences in regulatory foundations, appointment systems, and follow-up mechanisms among BPK, the Board of Audit, GAO, and ANAO, all of them have important roles in ensuring proper financial management. Additionally, the article proposes an alternative model for appointing members of the Republic of Indonesia Financial Audit Board (BPKRI) based on the experience of the U.S. GAO. This mechanism includes forming a commission comprising legislative, executive, and academic representatives to recommend BPK member candidates, aiming to enhance the independence of financial supervisory institutions in Indonesia